Integrating the Pancasila Student Profile into Islamic Religious Education Lesson Design at an Indonesian Public Elementary School - Aili Mufidatun; Ulfa Adilla; Andryadi; Novi Riani; Tiara Olivia (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2021)
The Indonesian Merdeka Curriculum positions the Pancasila Student Profile (PSP) as the central framework for character formation, yet empirical evidence on how elementary school teachers translate its six dimensions into Islamic Religious Education (PAI) lesson design remains limited. This study examines the extent of PSP integration in PAI lesson design at SD Negeri 100/II Muaro Bungo, Jambi Province, and identifies the institutional and pedagogical factors that shape its enactment. A qualitative descriptive-exploratory case study was conducted between February and May 2025, involving one PAI teacher, one school principal, and twelve students from grades IV–VI selected through purposive sampling. Data were generated through fifteen semi-structured interviews of approximately 60 minutes each, six classroom observations of 90 minutes each, and document analysis of the Capaian Pembelajaran (Learning Outcomes), Tujuan Pembelajaran (Learning Objectives), Alur Tujuan Pembelajaran (Learning Trajectory), and six teaching modules. Audio was captured at 44.1 kHz using a recorder with ±0.5 dB SPL accuracy. Data were analyzed using the Miles and Huberman interactive model, with credibility established through source, technique, and time triangulation. The teacher articulated five of six PSP dimensions during interviews, but only the dimensions of faith and piety with noble character (89%) and mutual cooperation (67%) were explicitly mapped into the analyzed lesson documents; critical reasoning, creativity, and global diversity appeared in fewer than 20% of plans. Three recurring barriers were identified: limited Merdeka Curriculum training (under 24 hours per teacher in the past three years), absence of context-specific learning resources, and an unformalized character-habituation routine at the school level. Effective PSP integration in elementary PAI requires explicit dimension-to-objective mapping in lesson templates, sustained teacher professional development, and a coordinated school family partnership for value habituation.